2011
DOI: 10.1016/j.jvs.2010.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access Carotid Endarterectomy can be Performed in the Hyperacute Period without a Significant Increase in Procedural Risks

Abstract: The VIRTUE Registry of Type B Thoracic Dissections -Study Design and Early ResultsThe VIRTUE Registry Investigators. Eur J Vasc Endovasc Surg 2011;41:8-15. Introduction: Endovascular procedures for repair of Type B aortic dissection have become increasingly common and are often considered to be first line therapy for acute complicated dissections. The long term durability of these repairs is largely undefined.Methods: The Virtue Registry is a prospective, non-randomised, multi centre European Clinical Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 0 publications
2
43
0
3
Order By: Relevance
“…We showed that performing CEA as early as 3 to 14 days after the qualifying neurological event was safe compared with later surgery in agreement with recent studies. 19,[25][26][27] Our data thus support recent changes in guidelines advocating the need for early intervention. 16 However, we also found that CEA performed 0 to 2 after the qualifying event was associated with a 4-fold higher procedural risk compared with surgery performed at 3 to 7 days.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We showed that performing CEA as early as 3 to 14 days after the qualifying neurological event was safe compared with later surgery in agreement with recent studies. 19,[25][26][27] Our data thus support recent changes in guidelines advocating the need for early intervention. 16 However, we also found that CEA performed 0 to 2 after the qualifying event was associated with a 4-fold higher procedural risk compared with surgery performed at 3 to 7 days.…”
Section: Discussionsupporting
confidence: 81%
“…Studies that report risk in urgent (0 -2 days) CEA are very few and include only a small number of patients. [17][18][19] The aim of this study was to determine the procedural risk of CEA for symptomatic carotid stenosis in relation to the time from the qualifying neurological event in a large population-based cohort. We also used a multivariate logistic regression analysis to find predictors of the risk of stroke and death within 30 days of CEA.…”
mentioning
confidence: 99%
“…A fuller description of the service has been detailed elsewhere. 7 The protocol advises the referring Family Doctor or Emergency Department to administer 300 mg aspirin and 40 mg simvastatin to all patients with a suspected TIA at the time of being seen and these medications were continued until the patient was seen in the Clinic. In the TIA Clinic, patients underwent CT/ MR imaging plus carotid ultrasound imaging and they were then seen by a consultant who specialized in stroke medicine.…”
Section: Rapid Access Tia Clinicmentioning
confidence: 99%
“…One of the goals was to ensure that patients suffering a TIA/minor stroke underwent CEA as soon as possible after onset of symptoms. 7 To facilitate expedited CEA, patients with an ipsilateral 50e 99% stenosis (NASCET measurement method) were commenced on optimal medical therapy in the TIA Clinic and then transferred directly to the Vascular Unit for expedited CEA. No provision for weekend operating was included in the protocol, but two half-day theatre lists (Tuesdays/Fridays) were kept free for urgent CEAs.…”
Section: Introductionmentioning
confidence: 99%
“…Many randomized trials have shown the bene it of early carotid revascularization for symptomatic carotid stenosis in stable patients [4]. According to recent literature, carotid revascularization (CR) should be performed within the irst two weeks following transient ischemic attack (TIA) or minor stroke, [5][6][7][8] and to some extend in the hyperacute period, within 48 hours [9,10]. In contrast, regarding major strokes or ongoing strokes, major studies recommend that surgery should be delayed four to six weeks after the irst neurological symptoms when clinical and radiological lesions have stabilized [11,12].…”
Section: Introductionmentioning
confidence: 99%